Characteristics and Histopathological Grading of Malignant Spiculated Mass in regards to Histopathological Grading of Breast Cancer Based on The Nottingham Grading System - Andi Syarti; Ulinta Pasaribu; Dyah Fauziah; Lies Mardiyana; Tri Wulanhandarini (Biomolecular and Health Science Journal, 2020)
Introduction: Spiculation in mammography is a typical finding for invading breast cancer and is an important criterion in diagnosis and in predicting prognostic and plays an important role in management. The purpose of this research is to determine the characteristics of malignant spiculating mass in mammography in regards to histopathological grading using The Nottingham Grading System.Methods: Patients whom had spiculation in mammography was reviewed using medical record data by two breast imaging consultants and then combined with The Nottingham Grading System criteria obtained from histopathological examination results of core biopsy and surgery specimen. There was 29 cases that met the inclusion criteria.Results: Of the 29 patients that met the inclusion, the spiculated masses grade I, II has mitotic index of 0-12, grade III has mitotic index of 13-25. Histopathologic grade II, III has the most tubular formation of <10%, grade I has 10-75%. Grade I, II has moderate nuclear pleomorphism, grade III has severe nuclear pleomorphism. Most were grade III (44.8%), followed by grade II (37.9%), and minimally grade I (17.2%). Most patients are in stage 3 breast cancer.Conclusion: Malignant spiculated mass with grade I, II has low proliferation index (mitotic index 0-12), histopathological grade II, III had worse cellular differentiation (tubular formation <10%), histopathological grade II, III has moderate to severe nuclear pleomorphism.